“SI PETRUK: SISTEM INFORMASI PENDAMPINGAN TERAPI TUBERKULOSIS” SEBAGAI INOVASI PENDUKUNG PENGOBATAN PASIEN TUBERKULOSIS - Widada, Subrata Tri; Siti Nuryani; Rita Rena Pudyastuti (Journal of Innovation Research and Knowledge, 2024)
Tuberculosis (TB) is a chronic disease caused by the bacterium Mycobacterium tuberculosis. In this case, tuberculosis is caused by a bacterial infection that attacks the respiratory tract of the lungs. Treatment of TB can be time-consuming and complex, as patients must undergo appropriate and disciplined drug therapy. Tuberculosis can be cured with treatment for six months to a year. In addition, TB patients also need good support and assistance in undergoing treatment. In the context of innovations supporting the treatment of TB patients, an information system called "Si Petruk" has been developed. Si Petruk is a tuberculosis therapy assistance information system that aims to help improve the effectiveness of TB treatment and reduce mortality from TB. The effectiveness of using applications is also supported by research (Purnomo, et al., 2020). That the application can optimize public services. This information system is designed to collect TB patient data electronically, including information about treatment status and laboratory test results. The system also provides automatic reminders to take medication and control appointments, as well as provides counseling and educational support for patients and families. In addition, Si Petruk also allows health workers to monitor and manage TB patients' treatment more effectively, by providing accurate information about treatment status and patient progress. The survey conducted on 43 tuberculosis patients showed that the Si Petruk application was useful with a value of 3.74 out of 4, ease of treatment of patients 3.58 out of 4, and ease of obtaining information of 3.6 out of 4. Then, the author also conducted a survey of 47 non-tuberculosis patients as a preventive measure for this disease showing that the Si Petruk application was useful with a value of 3.72 out of 4, easier for patients to educate 3.62 out of 4, and ease in obtaining information by 3.57 out of 4. The results of the following survey show that the Si Petruk application helps patients and non-patients to accompany treatment and educate tuberculosis.